Keabsahan Tafwīḍ Talak dalam Tinjauan Fikih Munākaḥāt (Studi Komparatif Pandangan Ibnu Qudamah dan Ibnu Hazm) - Akhmad Hanafi Dain Yunta; Saifullah Bin Anshor; Moh. Abduh Eing Paramata (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This research aims to find out and understand Ibn Hazm's views regarding tafwīḍ talak to wives. The type of research used in this research is qualitative descriptive research (non-statistical) using the library research method (literature review). The literature review contains theories that are relevant to the research problem. In this section, an assessment of the theoretical concepts used is carried out based on available literature, especially from articles published in various scientific journals. Qualitative research focuses on the general principles that underlie the manifestation of symptom units that exist in human life. The results of this research found that the discussion on the validity of tafwīḍ talak between the opinions of Ibn Qudamah and Ibn Hazm had differences of opinion, Ibnu Qudamah said that tafwīḍ talak was permissible and that talak was valid based on the word of Allah SWT. in Q.S. al-Ahzab/33: 28-29, hadith of 'Ᾱisyah ra. which was narrated by Muslim and Ijma' which relies on the Ᾱisyah hadith. Ibn Qudamah also believes that tafwīḍ talak is permissible and valid, so when a husband hands over his right to talak to his wife, this right remains the wife's right as long as it is not canceled by the husband. Meanwhile, Ibn Hazm believes otherwise, because according to him divorce is only for men. Ibn Hazm's opinion is more inclined towards the rights and obligations of men as heads of the household, so these rights cannot be given to women.